Novice and Experienced EFL Teachers: Which Professional Development Programs Matters for Our Classroom? - Shandra Nitalinawati (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This study aimed at exploring the perceptions of EFL novice and experienced teachers on the impact of professional development programs to their teaching practice. The design of this study is a descriptive study by using in-depth interviews for gaining the data. The result of this study revealed that novice and experienced teachers have different needs in developing their professionalism. This differences then lead to different preferences of development programs which really fulfill their needs and influence their teaching practice. Meanwhile, both teachers agree that the time permission is the most important factor of a successful development programs for teachers.Abstrak: Penelitian ini menyelidiki persepsi guru Bahasa Inggris pemula dan guru berpengalaman dalam dampak kegiatan pengembangan keprofesian terhadap kegiatan pembelajaran mereka. Metode yang digunakan dalam penelitian ini adalah metode wawancara mendalam dengan pertanyaan-pertanyaan terbuka. Hasil dari penelitian ini menunjukkan bahwa guru bahasa Inggris pemula dan berpengalaman memiliki kebutuhan yang berbeda dalam mengembangkan profesionalisme mereka. Perbedaan ini kemudian mengarah pada perbedaan pilihan kegiatan pengembangan keprofesian.